Through the ever night - Rossi, Veronica (New York Harper, 2013)
It's been months since Perry was named Blood Lord of the Tides, and Aria was charged with an impossible mission; now they are about to be reunited. But their reunion is far from perfect. The Tides don't take kindly to Aria, a former Dweller. And with the worsening Aether storms threatening the tribe's precarious existence, Aria begins to fear that leaving Perry behind might be the only way to save them both.
Sequel to: Under the never sky.
Donated by Jowana B. Bueser
Keywords: Dystopias; Young adult fiction; Fantasy fiction; Romance fiction